Pharmaceutical botany : a text-book for students of pharmacy and science - Youngken, Heber W. (Philadelphia, Pennsylvania : P. Blakiston's Son & Co., 1921)
This book was originally published prior to 1923, and represents a reproduction of an important historical work, maintaining the same format as the original work. While some publishers have opted to apply OCR technology to the process, we believe this leads to sub-optimal results and does not adequately preserve the historical characters of the original artifact.
Chapter I. Fundamental considerations -- Chapter II. Life history of the male fern -- Chapter III. Life history of a gymnosperm -- Chapter IV. Life history of an angiosperm -- Chapter V. Vegetable cytology -- Chapter VI. Plant tissues -- Chapter VII. Plant organs and organisms -- Chapter VIII. Taxonomy -- Chapter IX. Ecology.
Includes bibliographical references and index.
Keywords: BOTANY